THE EFFECT OF STUDENT PRESENTATION ON THE ELEVENTH GRADE STUDENT’S SPEAKING SKILL AT SMA NEGERI 24 KABUPATEN TANGERANG - Retno Puji Astuti; Abdul - Rohim (Universitas Muhammadiyah Tangerang, 2018)
AbstractREFERENCESBenyamin, H. (2012). Advanced Learning English 2 for Grade XI Senior High School. Bandung: Grafindo Media Pratama.Biadoll123. (2014). “Effective Presentation Skill” Journal Education-Business: 1-30. http://www.slideshare.net/biadoll123/effective-presentation-skills-29762969 (Accessed on January, 7th, 2014)Brown, D. H. (2003). Language Assessment Principles and Classroom Practices. California: Longman.—————. (2004). Language Assessment Principles and Classroom Practices. California: Longman.Chomsky, N. (2006). Language and Mind. Third Edition. New York: Cambridge University PressColman, M, A. (1996). “Teaching presentation skills to undergraduates: students’ evaluations of a workshop course.” Journal Education: 75-82. https://www2.le.ac.uk/departments/npb/people/amc/articles-pdfs/teacpres.pdf (Accessed on January, 2nd, 2016)Dewi, P,R. (on Friday, October, 2014) Presentasi. Accessed from http://dhytadwias.blogspot.co.id/2014/09/presentasi.htmlFakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Tangerang. (2015). Pedoman Penulisan Skripsi. Tangerang: UMT Pres.Fakultas Ekonomi Universitas Negeri Yogyakarta. (2014). Tantangan dan Keuntungan AFTA 2015 untuk Indonesia. Yogyakarta: WordPress.com.Gibson, M. (2013). Types of Presentations. Arkansas: Henderson State University. https://www.accuconference.com/blog/types-of-presentations/ (Accessed on October, 25th, 2013)Griffiths, C. (2008). Lesson from Good Language Learners. New York: Cambridge University Press.Haber, G. (2008).”( Benefits of Student Verbal Presentations to the Class.” Journal English Teacher Network: 1. http://www.etni.org.il/etnirag/issue9/gilda_haber.htm (Accessed on December, 12th, 2015)Harmer, J. (2007). The Practice of English Language Teaching. Third Edition. English: Cambridge.Hughes, R. (2002). “The Effect of Intensive Communication Activities to Improve Novice Learners’ Oral Interaction Skill.” Journal of English: 135. http://www.paaljapan.org/resources/proceedings/PAAL10/pdfs/negishi.pdf (accessed on December, 1st, 2015)It’s Time to Go to School! Short Example of Spoof Text. (on June 2013) Accessed from http://freeenglishcourse.info/its-time-to-go-to-school-short-example-of-spoof-text/Louma, S. (2004). Assessing Speaking. Cambridge: Cambridge University Press.Mandel, S. (2000). Effective Presentation Skill. Boston: United States of America.Mutiara, M, N, S. (on January, 24th, 2016). Personal Interview.Nita, W, A. (2015). Effect of Presentation on the Eleventh Grade Student’s Speaking Skill at SMA 14 Kabupaten Tangerang. Program Sarjana Fakultas Keguruan dan Ilmu Pendidikan Bahasa Inggris. Tangerang: Universitas Muhammadiyah Tangerang.Pollard, L. (2008). Lucy Pollard’s Guide to Teaching English. London: University of London.Prabowo, D, A. (on January, 3th, 2013). Example of Spoof Text, Definition, Generic Structure, and Purpose. Accessed from http://di-copy.blogspot.co.id/p/about-us.htmlRiadi, E. (2014). Metode Statistika Parametrik & Nonparametrik. Tangerang: Pusaka Mandiri.Sriwismajayanti. (on July, 28th, 2010) Definition of Spoof Text. Accessed from https://sriwismajayanti.wordpress.comSugiono. (2013). Metode Penelitian Kuantitatif dan Kualitatif dan R&D. Bandung: Alfabeta.—————— (2003). Metode Penelitian Kuantitatif dan Kualitatif dilengkapi dengan R&D. Bandung: Alfabeta.Tornbury, S. (2005). How to Teach Speaking. Vermont: LongmanWallwork, A. (2010). English for Presentations at International Conferences. New York: Spinger.Yunita, N. (2014). Improving the Eleventh Grade of Administration Student’s Speaking Skill through Role Play Strategy at SMK Harapan Jaya Cengkareng. Program Sarjana Fakultas Keguruan dan Ilmu Pendidikan Bahasa Inggris. Tangerang: Universitas Muhammadiyah Tangerang